ANALISIS DETERMINAN ENTREPRENEURIAL ORIENTATION PADA USAHA KECIL MENENGAH (UKM) (Studi Pada Pemilik UKM Di Kota Pasuruan) - Bulky Muhammad Maharsa; Mohammad Iqbal (Fakultas Ilmu Administrasi Universitas Brawijaya, 2017)
Entrepreneurial Orientation is part of the Enterprise. This is part of the entrepreneurial process. Entrepreneurial Orientation understand the phenomenon as one of the strengths of the organization to improve the course of the process can foster entrepreneurship and entrepreneurial behavior patterns are applied to maintain the business. Furthermore, entrepreneurial orientation can explain the overall picture of entrepreneurial activity by providing knowledge about the various dimensions of entrepreneurial orientation. There are five dimensions of entrepreneurial orientation is Inovativeness, proactiveness, risk taking (Miller, 1983), Autonomy Orientation and Competitive aggressiveness (Lumpkin & Dess, 1996). Based on extensive literature review and collection of empirical evidence, this study examines the extent to which small and medium enterprises (SMEs) in the city of Pasuruan and apply the concept of entrepreneurial orientation. In addition, this study explores the dominant factors in the entrepreneurial orientation that is applied to SMEs in Pasuruan. and as research that is confirmatory factor analysis on the opinion of Lumpkin and Dess (1996) which states all the factors in the entrepreneurial orientation possibility is present in a business organization, but not all factors are sometimes applied in business organizations, there are some things that are optimized to be a priority. Keywords: Entrepreneurial, Entrepreneurial Orientation, Small and Medium Enterprises ABSTRAK Entrepreneurial Orientation merupakan bagian dari Kewirausahaan. Tahap ini merupakan bagian dari proses kewirausahaan. Memahami fenomena Entrepreneurial Orientation sebagai salah satu kekuatan yang dimiliki organisasi untuk meningkatkan jalannya proses kewirausahaan dan dapat menumbuhkan pola perilaku kewirausahaan yang diterapkan untuk mempertahankan usaha. Lebih lanjut, entrepreneurial orientation dapat menjelaskan gambaran keseluruhan dari kegiatan kewirausahaan dengan memberikan pengetahuan tentang berbagai dimensi dari entrepreneurial orientation. Terdapat 5 Dimensi dari entrepreneurial orientation yaitu Inovativeness, Proactiveness, Risk taking (Miller, 1983), Autonomy Orientation dan Competitive Aggressiveness (Lumpkin & Dess, 1996). Berdasarkan tinjauan literatur yang luas dan pengumpulan bukti empiris, studi ini mengkaji sejauh mana suatu Usaha kecil dan menengah (UKM) yang ada di Kota Pasuruan mengetahui dan menerapkan konsep entrepreneurial orientation. Selain itu, penelitian ini mengekplorasi faktor-faktor dominan dalam entrepreneurial orientation yang di terapkan pada UKM di Kota Pasuruan. dan sebagai penelitian yang bersifat confirmatory factor analysis terhadap pendapat Lumpkin dan Dess (1996) yaitu menyatakan semua faktor-faktor dalam entrepreneurial orientation kemungkinan hadir dalam sebuah organisasi bisnis, tetapi tidak semua faktor terkadang diterapkan dalam organisasi bisnis, ada beberapa hal yang dioptimalkan untuk menjadi prioritas. Kata Kunci: Entrepreneurial, Entrepreneurial Orientation, Usaha Kecil Menengah